World Wide Video Festival 1983. - Kijkhuis, Den Haag; Studio 122, Den Haag; Galerie Artline, Den Haag; Haags Gemeentemuseum, Den Haag; World Wide Video Festival, Den Haag (Den Haag : Kijkhuis, 1983)
Stein, BetsyNewman & Ellin ; Bostrom, Denise ;Reeves,Dan;Mowbray, Edward ; Odenbach,Marcel ;Alpert,Jon ; Iatrou & Morgan ; Image, After ; Cohen, Maxi ; Adams, John ; Lupini, Saskia ; McDonald, Laurie ; Morifumi, Arimura ; Harrison, Julie ; Hafuij, You ; Hervé, Geneviève ; Idemitsu,Mako ; Shinohara, Yasuo ; Deutsch, Gustav ; Neuwirth, Gerda Lampalzer & Manfred ; Ikam, Catherine ; Schouten, Lydia ; Theuws, Roos ; Feist, Richard ; Weidenaar, Reynold ; André, Marie ; Paik, Nam June ; Kubota, Shigeko ; CIE, Michael Hazard & Jim Mulligan / The ; Matsumoto, Toshio ; Blumberg, Skip ; Rapid Deployment Theater Forces ; Ondulata, Serge Nicolas & Waving ; Nicolas, Serge ; Nicol, nancy ; Servaas ; IM, Studio ; Tomczak, Kim ; Lafontaine, Marie-Jo ; Shapiro, Celia ; Toebosch, Moniek ; Minh, Yann Nguyen ; Lord, Chip ; Barry, Judith ; Marton, Pier ; Belloir, Dominique ; Gorewitz, Shalom ; Densmore, Janet ; Kurotsuka, Naoko ; Weele, Ineke Van der ; Waving Ondulata (Guy Marc Hinant & Frédéric Walheer) ; Kracke, Bernd ; Wölfl, VA ; Almy, Max ; Longuet, Teresa Wennberg & Alain ; Jeffrenou, Michel ; Harding, Noel ; Tanaka, Janice ; ICTUS TV ; South West Media Collective ; Nicolas, Daniel Schell & Serge ; Brown, W.A. ; Hoover, Nan ; Martinis, Dalibar ; Casinière, Joëlle de la ; Studio, Open ; Van Dormael, Jaco ; Birnbaum, Dara ; Bousquet, Michel Jeffranou & Patrick ; Beaujour, Jean Mascolo & Jérôme ; Pain, François ; Marton, Michael ; Jaeggi, Jean-Paul Fargier & Danielle ; Sollers, Jean-Paul Fargier & Philippe ; Gautreau, Jean-Michel ; Geduldig, Bruce ; Bourges, Alain ; DeMontaut, Philippe ; Jaeggi, Daniëlle ; Kané, Pascal ; Viola, Bill ; Johansen, Kirsten ; Cahen, Robert ; Oursler, Tony ; Kuntzel, Philippe Grandrieux & Thierry ; Alemann, Claudia von ; etc.
World Wide Video Festival, Kijkhuis, Den Haag / Studio 122, Den Haag / Galerie Artline, Den Haag / Haags Gemeentemuseum, Den Haag, 1983
boek